Effects of Weight Resistance Training on Swimmers with Down Syndrome - Fabián Víquez Ulate y Andrea Mora Campos (FEADEF, 2011)
The objective of this study was to determine the effect of weight resistance training on strength in swimmers with Down Syndrome (DS). Seven swimmers with DS participated in the study: 6 men and 1 woman, 23.14 years of age ± 4.59 and with 6.14 years ± 2.34 years of swimming. Instruments: One repetition maximum (RM) test to determine the individual's maximum muscular strength. Procedure: the study was conducted for 10 weeks (2 weeks at baseline, 6 weeks of treatment and 2 weeks to see the effects of retention). Results: significantly positive changes were detected in the maximum strength of pectoral muscles (F=5.768; p=0.006), dorsal muscles (F = 26.770; p=7.45e-007), femoral biceps (F = 32.530; p=1.76e-007), quadriceps (F = 8.391; p=0.001), triceps (F = 11.217; p=0.0002) and these adjustments were maintained with no significant changes for two weeks, while the biceps muscle (F=4.145; p=0.021) behaved differently since it suffered no significant adjustments during the program.